ANALISIS PEMANFAATAN MEDIA SOSIAL TIKTOK UNTUK MENINGKATKAN MINAT BELI KONSUMEN SECARA ONLINE PADA BRAND SOMETINC OFFICIAL - Anggraini, Nimas Ayu; Hindra H, Nurnawati; Sihabuddin, Sihabuddin (Solidaritas, 2024)
The rapid development of communication technology has also led to the development of communication media from conventional media to a social media platform. This development is then utilized by business actors to carry out promotional activities through social media for products. One of the media that is considered appropriate to use at this time is TikTok, TikTok media is considered to have promising prospects because its users are increasing day by day and is also popular among young people. Based on this description, researchers are interested in conducting research on how the Somethinc official brand strategy increases consumer buying interest through its TikTok account as a marketing tool. The research method used is documentation and interviews with Resellers and female students domiciled in Soloraya. The findings in this study highlight the importance of promoting a product on TikTok to build consumer awareness, and that TikTok has an important role in increasing consumer awareness and buying interest, thus showing the potential of the TikTok social media platform as an effective marketing tool for a business. Keywords: Social media, Marketing, TikTok, Buying Interest